Crosstalk between ferroptosis and steroid hormone signaling in gynecologic cancers - Lai, Wen; Chen, Jianquan; Wang, Tianming; Liu, Qiaoling (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a novel types of regulated cell death and is widely studied in cancers and many other diseases in recent years. It is characterized by iron accumulation and intense lipid peroxidation that ultimately inducing oxidative damage. So far, signaling pathways related to ferroptosis are involved in all aspects of determining cell fate, including oxidative phosphorylation, metal-ion transport, energy metabolism and cholesterol synthesis progress, et al. Recently, accumulated studies have demonstrated that ferroptosis is associated with gynecological oncology related to steroid hormone signaling. This review trends to summarize the mechanisms and applications of ferroptosis in cancers related to estrogen and progesterone, which is expected to provide a theoretical basis for the prevention and treatment of gynecologic cancers.